Analisis Overall Equipment Effectiveness (OEE) dan Failure Mode and Effect Analysis (FMEA) pada Mesin Packer - Anggraeni, Salsabila Nur; Dewanto, Dhesta Laurent; Jaya, Satria (nter of Execellence (COE) ICT Infrastructure, Smart Manufacture and Digital Supply Chain, 2025)
The study on the effectiveness and reliability of the packer machine at PT. XYZ through the calculation of Overall Equipment Effectiveness (OEE) and Failure Mode and Effect Analysis (FMEA) aims to determine the performance percentage of the packer machine at PT. XYZ. Data was collected from Packer Machine 8 in the Packhouse Department during the period from January to June 2024. The OEE calculation results showed an average value of 66%, which falls within the acceptable classification. However, further analysis is needed to improve machine effectiveness and prevent further decline. Analysis using the Pareto diagram and Fishbone diagram revealed that clogging in the machine's spout due to clumped cement particles is the main cause of failure. FMEA was utilized to identify causes and corrective actions, with a focus on enhancing maintenance schedules, routine maintenance, and strict SOP implementation. The implementation of these improvements is expected to increase the effectiveness and reliability of the packer machine at PT. XYZ